2009
DOI: 10.3109/07380570903329644
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Program Development and Evaluation Through a Service Learning Project in Community-Based Adult Day Services

Abstract: This paper examines an instructional methodology, service learning, as a method for teaching program development and evaluation in adult day service centers. Adult day service, an emerging practice area, provides an opportunity for students to learn program development while they explore and meet the occupational needs of elders living in the community. Students learn to design and implement day service activities to benefit both the agencies and people they are serving. In this study, 39 students were surveye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…This finding was consistent with previous studies that have recommended community-based FW to increase awareness of practice options and better prepare students to enter less traditional settings (Adam et al, 2014, Hanft & Anzalone, 2001, Holmes & Scaffa, 2009a, Holmes & Scaffa, 2009bRamsey, 2011). There is clearly support among community-based clinicians and researchers for more FW opportunities, and several studies have suggested the efficacy of non-traditional FW placements (Dillon, Dillon, King, & Chamberlin, 2007;Gat & Razon, 2014;Schaber, 2010). However, incorporating more community-based FW into OT education can be challenging due to the limited number of community-based OTs to serve as supervisors (Holmes & Scaffa, 2009b) and the need to meet specific accreditation standards.…”
Section: Suggestions For Improving Academic Training and Continuing Esupporting
confidence: 89%
“…This finding was consistent with previous studies that have recommended community-based FW to increase awareness of practice options and better prepare students to enter less traditional settings (Adam et al, 2014, Hanft & Anzalone, 2001, Holmes & Scaffa, 2009a, Holmes & Scaffa, 2009bRamsey, 2011). There is clearly support among community-based clinicians and researchers for more FW opportunities, and several studies have suggested the efficacy of non-traditional FW placements (Dillon, Dillon, King, & Chamberlin, 2007;Gat & Razon, 2014;Schaber, 2010). However, incorporating more community-based FW into OT education can be challenging due to the limited number of community-based OTs to serve as supervisors (Holmes & Scaffa, 2009b) and the need to meet specific accreditation standards.…”
Section: Suggestions For Improving Academic Training and Continuing Esupporting
confidence: 89%
“…The occupational therapy literature provides numerous accounts of strategies for developing service-learning courses for occupational therapy students, along with in-depth analyses of the pedagogical benefits of doing so (Alsop, 2007;Atler & Gavin, 2010;Beck & Barnes, 2007;Flecky & Gitlow, 2011;Gitlow & Flecky, 2005;Hansen et al, 2007;Hoppes, Bender, & DeGrace, 2005;Maloney & Griffith, 2013;Marken, Moxley, & Fraley, 2011;O'Brien & D'Amico, 2004;Olivier, Oosthuizen, & Cateleijn, 2007;Schaber, 2010;Schindler, 2011;Vroman, Simmons, & Knight, 2010). Greene (1997), in one of the earliest accounts of the benefits of service-learning, found the students reported increases in their awareness of diversity and insight 146 S. M. Maloney et al into the lived-experiences of persons with disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to providing students with potential valuable pedagogical experience of building strong bridges, strengthening intergenerational relations (Alcón, 2016). Service Learning produces outcomes related to character development and citizenship education when done well (Schaber, 2010). Therefore, this study aims to analyze how Service Learning is implemented in Indonesia at Senior Secondary School.…”
Section: Introductionmentioning
confidence: 99%